2003
DOI: 10.1182/blood-2002-11-3333
|View full text |Cite
|
Sign up to set email alerts
|

CD20 is associated with a small mature plasma cell morphology and t(11;14) in multiple myeloma

Abstract: CD20 has been reinvestigated in 66 patients with multiple myeloma (MM). Twelve of the patients (18%) expressed CD20, including 5 of 50 patients at diagnosis presenting 100% CD20 ؉ cells. Seven (58%) of 12 CD20 ؉ patients with MM had a small mature plasma cell morphology as opposed to 4 (7%) of 54 with CD20 ؊ MM (P ‫؍‬ .0001). Of note, 10 (83%) of 12 patients with CD20 ؉ MM had t(11;14) as opposed to 5 of 54 (9%) CD20 ؊ patients (P < .001). All the patients with 100% CD20 ؉ cells presented with t(11;14) and 4 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
100
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(112 citation statements)
references
References 12 publications
10
100
1
1
Order By: Relevance
“…In this context, t (11:14) has been shown to correlate with expression of CD20 (38). Consistent with this finding, we detected an association between overexpression of cyclin D1, but not cyclin D2 or D3, with t(11:14) by fluorescence in situ hybridization (Table 2) and strong CD20 expression on all cyclin D1-expressing multiple myeloma cells ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…In this context, t (11:14) has been shown to correlate with expression of CD20 (38). Consistent with this finding, we detected an association between overexpression of cyclin D1, but not cyclin D2 or D3, with t(11:14) by fluorescence in situ hybridization (Table 2) and strong CD20 expression on all cyclin D1-expressing multiple myeloma cells ( Fig.…”
Section: Discussionsupporting
confidence: 87%
“…The data about the expression of CD20 on PCs of healthy people is conflicting (15,16). We found that the proportion of CD20 expressing PCs was highly variable from case to case in HDs and MM patients.…”
Section: Cd20mentioning
confidence: 95%
“…Also, other common features have been reported in both MM subsets, that is, lower secreting capacity, CD20 expression and association with IgM isotype. [9][10][11] On the other hand, both immature morphology and t(4;14) correlated with some adverse prognostic factors, including high tumor mass and C13A, whatever the presence or absence of plasmablasts. In addition, higher serum level of sIL6-R, b 2 M and PC proliferative indices have been reported in both t(4;14) and plasmablastic MM subtypes.…”
Section: Discussionmentioning
confidence: 99%